The Role of Organic Marketing on Instagram in Influencing Consumer Purchase Decisions: A Case Study of Kopi Kenangan - Rahman, Dimas Aulia; Mutasowifin, Ali (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study investigates the impact of organic marketing on consumer purchasing decisions using a case study of Kopi Kenangan, a leading coffee chain in Indonesia. The research analyzes how Instagram features like Feed, Stories, Reels, and Live influence consumer behavior. A total of 100 Instagram users who have purchased Kopi Kenangan products were surveyed through an online questionnaire. The data were analyzed using descriptive statistics and the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results show that Instagram Feed and Instagram Stories significantly positively affect purchasing decisions, while Instagram Reels and Live do not show a significant impact. The findings highlight the effectiveness of unpaid digital marketing efforts in shaping consumer preferences and suggest that businesses can leverage organic content on Instagram to enhance customer engagement and drive sales.